Self-Help Group on Quality of Life of Patients Treating Chemotherapy - Sylvia Marlina Turnip; Kiking Ritarwan; Nunung Febriany Sitepu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The self-help group is one of the group therapies which provides social and psychological support for its members since they can share their problems, and information about nursing, prevention, and medication. The study was to identify the influence of self-help groups on the life quality of patients under chemotherapy treatment. The study was a quasi-experimental method with a pretest-posttest without a control group design. The samples were 35 patients under chemotherapy treatment using the purposive sampling technique. The data were gathered by using a questionnaire, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-C30) pre and post-intervention. The data were analyzed by using Wilcoxon Signed Rank Test. The study showed that there was a significant influence on the quality of life of those who were under chemotherapy treatment after self-help group intervention (p=0.000). It is recommended that the hospital management evaluate the life quality of the patients under chemotherapy treatment regularly. The nursing education department should make self-help groups the subject materials for the students as one of the nursing interventions. Abstrak: Self-help group adalah salah satu terapi kelompok yang memberikan dukungan sosial dan psikologis bagi anggotanya karena mereka dapat berbagi masalah, informasi tentang keperawatan, pencegahan, dan pengobatan. Penelitian ini bertujuan untuk mengidentifikasi pengaruh kelompok swadaya terhadap kualitas hidup pasien yang menjalani pengobatan kemoterapi. Penelitian ini merupakan penelitian eksperimen semu dengan metode pretest-posttest without control group design. Sampel penelitian adalah 35 pasien yang menjalani pengobatan kemoterapi dengan teknik purposive sampling. Data dikumpulkan dengan menggunakan kuesioner, European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-C30) sebelum dan sesudah intervensi. Analisis data menggunakan Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan terhadap kualitas hidup mereka yang menjalani pengobatan kemoterapi setelah intervensi kelompok swadaya (p=0,000). Direkomendasikan agar manajemen rumah sakit mengevaluasi kualitas hidup pasien yang menjalani pengobatan kemoterapi secara teratur. Jurusan pendidikan keperawatan sebaiknya menjadikan kelompok swadaya sebagai bahan ajar mahasiswa sebagai salah satu intervensi keperawatan.